가상현실기반 낙하훈련시스템 개발 - 유재정(Jae-Jeong Ryu); 강석중(Seok-Joong Kang) (한국정보통신학회논문지, 2021)
Virtual reality is actively applied in the fields of games, entertainment, communication, sports, and architecture. In particular, many virtual reality-based education systems are being developed in the field of education, creating efficient learning effects. In addition, virtual reality-based education is used in areas such as maintenance, fighter control, medical care, and firefighting as it can maximize the educational effect through the mastery process of the function itself through the curriculum as well as indirect experiences of dangerous situations that are difficult to experience. However, due to technical limitations, lack of contents, and lack of theoretical research, the level of application of military education and training is still insufficient. This paper aim to contribute to the development of a virtual reality-based education system as a military training system by developing a high-quality drop training system applicable to military group descent training, studying key technologies and implementation methods necessary for development. 가상현실은 게임, 오락, 통신, 스포츠, 건축 분야에서 활발히 적용되고 있다. 특히 교육 분야에도 많은 가상현실 기반의 교육 시스템이 개발되고 있어 효율적인 학습효과를 만들어내고 있다. 그러나 기술적 한계, 콘텐츠의 부족, 이론적 연구 부족 등으로 인해 아직은 군사용 교육 훈련 부분 적용되기에는 수준이 부족한 상태이다. 본 논문에서는 군사용 집단 강하 훈련에 적용 가능한 수준 높은 낙하훈련시스템을 개발하고, 개발에 필요한 핵심 기술과 구현방법을 연구하였으며, 개발 결과에 따른 효과를 분석하여 군사용 훈련시스템으로서의 가상현실기반 교육 시스템의 발전에 이바지하고자 한다.